A Proposal of a Universal Remote Control System Based on Head Movements - Batista, Cassio T. Batista; Campos, Erick M. Campos; Neto, Nelson C. Sampaio Neto (Teste; 2018: IHC_21, 2018)
Technological developments converge to make people interact with electronic devices in an easy way. For people with disabilities, however, that interaction becomes something more than simple: it becomes possible. The current work presents a proposal of an open-source, low cost universal remote control system that translates user's head poses into commands to electronic devices. In addition, a proximity sensor circuit was combined to radio-frequency modules in order to act as a wireless switch. Among the applications found with respect to alternative remote controls, none of them supports head gestures as input, which would certainly make them a viable option to people whose upper limbs are compromised. A mean opinion score questionnaire was applied to volunteers in order to evaluate the system. The results show great interest of the users in this kind of technology.